Research participants’ perception of ethical issues in stroke genomics and neurobiobanking research in Africa - Jegede, Ayodele; Balogun, Olubukola; Olorunsogbon, Olorunyomi Felix; Nichols, Michelle; Akinyemi, Joshua; Jenkins, Carolyn; Ogunronbi, Mayowa; Singh, Arti; Obiako, Reginald; Wahab, Kolawole; Bello, Abiodun; Akpalu, Albert; et al. (PloS one, 2025)
There is a growing interest in stroke genomics and neurobiobanking research in Africa. These raise several ethical issues, such as consent, re-use, data sharing, storage, and incidental result of biological samples. Despite the availability of ethical guidelines developed for research in Africa, there is paucity of information on how the research participants' perspectives could guide the research community on ethical issues in stroke genomics and neurobiobanking research. To explore African research participants' perspectives on these issues, a study was conducted at existing Stroke Investigation Research and Education Network (SIREN) sites in Nigeria and Ghana. Using an exploratory design, twenty-eight Focus Group Discussions (FGDs) sessions were conducted with stroke survivors (n = 7), caregivers(n = 7), stroke - free controls(n = 7), and Community Advisory Board members(n = 7). Data were collected using an interview guide. Interviews were conducted in English and indigenous languages of the community, audio recorded, and transcribed verbatim. Data were analyzed using NVivo (March, 2020) Software. Results revealed that stroke genomics and neurobiobanking research in Africa require researchers' direct attention to ethical issues. Concerns were raised about understanding, disclosure and absence of coercion as components of true autonomous decision making in research participation. Participants argued that the risk and benefits attached to participation should be disclosed at the time of recruitment. Fears around data sharing were voiced as adherence to the principle of privacy and confidentiality were of paramount importance to participants. The preference was to receive the results of incidental findings with no stigma attached from society. Research participants' perspectives are a vital aspect of community engagement in stroke genomics and neurobiobanking research. Findings from this study suggest that research participants are interested in these fields of research in Africa if their concerns about ethical issues are appropriately addressed within the research framework.